2016
DOI: 10.1159/000445439
|View full text |Cite
|
Sign up to set email alerts
|

The Early Mother-to-Child Bond and Its Unique Prospective Contribution to Child Behavior Evaluated by Mothers and Teachers

Abstract: Maternal bonding has been described as the quality of the affective tie from a mother to her infant. This early bond's mental components and its longitudinal impact on child outcome have been markedly understudied. Although most researchers assume impaired maternal bonding to have a negative impact on child development, there is a lack of prospective studies evaluating this hypothesis. Since maternal mental health problems may negatively affect both bonding quality and child development, it is still to be dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 40 publications
0
29
0
2
Order By: Relevance
“…Future studies could investigate whether a traumatic birth in which fears were realised mediates the relationship between FOC and postnatal bonding and whether problems persist. Perceived difficulties in bonding measured by the PBQ have been associated with parental stress and negative child outcomes (de Cock et al 2017;Fuchs et al 2016). Perceived bonding is therefore of likely clinical importance, and the PBQ could be a useful way to identify dyads at risk of future issues.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could investigate whether a traumatic birth in which fears were realised mediates the relationship between FOC and postnatal bonding and whether problems persist. Perceived difficulties in bonding measured by the PBQ have been associated with parental stress and negative child outcomes (de Cock et al 2017;Fuchs et al 2016). Perceived bonding is therefore of likely clinical importance, and the PBQ could be a useful way to identify dyads at risk of future issues.…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in forming close and secure social bonds is a common feature of psychopathology, and may be a precursor to problem behavior. For instance, social competence at age 4 predicts subsequent internalizing and externalizing symptoms (Bornstein, Hahn, & Haynes, 2010) and the quality of mother-infant bonds at 2 weeks predicts child behavior problems at age 5 (Fuchs, Möhler, Reck, Resch, & Kaess, 2016). Likewise, the establishment of close relationships due to enriched early experiences of contact may enhance resilience, as social support has been shown to buffer the effects of stress (Hostinar, Sullivan, & Gunnar, 2014).…”
Section: Implications Of Findings For Psychopathologymentioning
confidence: 99%
“…The development of bonding is important, as impaired bonding can impact the child's emotional, cognitive, and behavioral long-term development. For example, studies have shown associations between impaired mother-to-infant bonding and child behavior problems in early childhood [5], and an increased child's risk of developing psychopathology in adulthood [6]. Moreover, mothers who reported impaired mother-to-infant bonding experienced high levels of parenting stress during toddlerhood [7], and these children are at risk for maltreatment later in life [8].…”
Section: Introductionmentioning
confidence: 99%